Korelasi antara Kolesterol Total dengan Kadar HbA1c pada Pasien Diabetes Mellitus Tipe 2 di RSUD Tabanan Tahun 2021 - Ni Nyoman Trisna Haryanti; Sri Ratna Dewi; Putu Nia Calista Santoso (Aesculapius Medical Journal, 2023)
Diabetes mellitus (DM) is chronic disease associated with various complications. Measurement of glycosylated hemoglobin (HbA1c) can be used as a standard for monitoring and risk indicators for DM complications. Increased levels of Free Fatty Acid (FFA) cause total cholesterol in type 2 DM to increase. Several studies have shown different results regarding the relationship between total cholesterol and HbA1c levels, so researchers are interested in re-examining the correlation of total cholesterol with HbA1c in type 2 DM patients. This research re-examined the correlation of total cholesterol and HbA1c levels in type 2 DM patients. The research was carried out which aimed to determine the correlation of total cholesterol with HbA1c in type 2 DM patients at Tabanan Hospital in the period January 1st – December 31st, 2021. This type of research is cross-sectional analytic observational research from secondary data sources (medical records) taken by consecutive sampling. Then the data was analyzed using the Pearson test through Statistical Product and Service Solutions (SPSS). Based on research starting in August-November 2022, samples that met the inclusion and exclusion criteria were 54 samples. From these samples, the average total cholesterol level was 225 mg/dl and the average HbA1c level was 8.8%. Pearson correlation test results obtained r = 0.371 (weak positive correlation) and p-value = 0.006, therefore it can be stated that total cholesterol and HbA1c levels have a significant relationship in type 2 DM patients.